COMPLICATIONS OF GALLSTONE DISEASE - VALERIY I. Podoluzhnyi (Фундаментальная и клиническая медицина, 2017)
The lecture describes the current understanding of cholelithiasis and its complications (acute cho- lecystitis, choledocholithiasis, papillolithiasis, stulas and gallbladder cancer), including: 1) clinical diagnosis, i.e. signs and symptoms; 2) laboratory diagnosis; 3) treatment